The Influence of Collaboration of Memorization Methods with Nahwu and Shorof on the Understanding of Al-Qur'an Hadith Subjects of Class X Students of Madrasah Aliyah Bumi Sholawat Wates - Muhamad Fuad Akbar; Ehwanudin, Ehwanudin; Eka Fitria Ningsih (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2025)
This study aims to analyze the effect of collaborative memorization method with Nahwu and Shorof science on the understanding of Al-Qur'an Hadith subjects. This study uses a quantitative research method with a One Group Pretest-Posttest design. The population in the study amounted to 90 students, and the sample used was 20 class X students selected through cluster random sampling technique. The research instrument was a test designed to measure students' level of understanding before and after treatment. The instrument has been tested for content validity and reliability using Cronbach's Alpha with the help of IBM SPSS version 30, the test results show sig 0.41> 0.05, it can be concluded that the instrument is reliable and can be used to obtain research data. The results of the paired sample T test show a sig value of 0.001 <0.05, so it can be concluded that there is a significant effect after applying the collaboration of memorization methods with Nahwu and Shorof in Al-Qur'an Hadith subjects for class X Madrasah Aliyah Bumi Sholawat Wates students. The results of data analysis show that there is an increase in student understanding after the application of this collaborative method, with an N-Gain score of 0.36 which is included in the moderate category. This finding indicates that the collaboration of memorization method with Nahwu and Shorof can significantly improve students' understanding of the Hadith Qur'an subject.